Perancangan Motion Graphic Dampak Plastik Di Laut - Eduard Bagas Pratama; Donna Carollina (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2020)
Discussion about the problem of world waste, especially plastic wastein the sea, is currently a seriously problem, especially in Indonesia.Indonesia is the second-largest contributor to plastic waste in theworld. Plastic waste in the sea takes 500-1000 years to completelydecompose. So that efforts need to be made to reduce the use ofplastic to prevent the destruction of Indonesia's marine ecosystem.The effort made by the writer is to design motion graphics. Motiongraphics become an educational medium for junior high schoolchildren about the impact of plastic in the ocean along with solutionsthat can be applied in everyday life.